Resurgence of the past: political and media discourse during the breakup of the former yugoslavia - Gregor Perko (Linguistica, 2018)
The wars and conflicts that accompanied the breakup of the former Yugoslavia are inextricably linked to “language”. The “breakup” of Serbo-Croat into several national languages and the determination of Slovenes and, to a lesser extent, Macedonians to restrain the influence of Serbo-Croat on their respective languages ​​was a prelude to the country’s political breakup. Military violence was carefully prepared by linguistic means: hate speech, which quickly turned into war speech, dominated the words of politicians, media, culture and everyday conversation. This would not have been possible without resorting to the past and to the mythologized history of the warring parties (the Battle of Kosovo Polje, Yugoslavia before the Second World War, the Second World War itself). The analysis of the political and media discourses carried out in this study revealed three major types of semantic inversions on which the underlying discursive mechanisms largely rely: diachronic inversions (the resurgence of the terms “Ustashe”, “Chetniks”, “Turks”), semantic and logical travesties (in which terms such as “defend” and “liberate” lose their primary meanings) and semantic asymmetries (the enemy is an inhuman “aggressor” and “slaughterer”, while “our” side is made up of “innocent victims”, “martyrs” or “heroes”). As a result, the terms and utterances used lose their semantic and referential “basis”, so that they can no longer fully function except within the discursive universe that generated them.